Developing listeners in the high school band classroom: using student-led rehearsals - Nations, Blake (My University, 2025)
The lessons demonstrated in this report are focused on using student-led rehearsals to improve high school band students’ listening abilities in respect to ensemble rhythmic accuracy, note accuracy, balance accuracy, and expression accuracy. Young musicians often do not know what they should be listening to in an ensemble setting and teachers normally have no way of assessing their listening abilities. These lessons incorporate student-led rehearsals with minimal teacher intervention to force students to listen to the ensemble to find inaccuracies that need corrected. I designed these lessons using ideas I gained from study during my master’s program in the areas of rehearsal techniques and score study. Using student-led rehearsals led to a positive outcome in two areas: students’ listening abilities improved throughout the lessons and students enjoyed making a piece of music fully their own that they were excited to share with parents and the community. During my time at K-State, I have developed my abilities and skills by adapting instruction to the specific students at my school. An example of these adaptations is that my band program paid for a drill writer to write drill. The difficulty and amount of drill that we received was too much for my program. I now write the drill for specific students in mind, not just shapes or dots on the field. I have also created leadership positions within both the marching band and concert band parts of my program at the junior high and high school level. Having these positions creates more buy-in from students and allows the program to run smoother overall while lowering my workload. This allows me to focus on what I want to focus on: making music. Making music in the high school classroom is easier with the students’ new leadership skills and their new listening skills that have been developed through student-led rehearsals
Keywords: Student-led rehearsals; High school band